How are learning strategies reflected in the eyes? Combining results from self‐reports and eye‐tracking. (29th August 2017) - Catrysse, Leen; Gijbels, David; Donche, Vincent; De Maeyer, Sven; Lesterhuis, Marije; Van den Bossche, Piet
Abstract : Background: Up until now, empirical studies in the Student Approaches to Learning field have mainly been focused on the use of self‐report instruments, such as interviews and questionnaires, to uncover differences in students' general preferences towards learning strategies, but have focused less on the use of task‐specific and online measures. Aims: This study aimed at extending current research on students' learning strategies by combining general and task‐specific measurements of students' learning strategies using both offline and online measures. We want to clarify how students process learning contents and to what extent this is related to their self‐report of learning strategies. Sample: Twenty students with different generic learning profiles (according to self‐report questionnaires) read an expository text, while their eye movements were registered to answer questions on the content afterwards. Methods: Eye‐tracking data were analysed with generalized linear mixed‐effects models. Results: The results indicate that students with an all‐high profile, combining both deep and surface learning strategies, spend more time on rereading the text than students with an all‐low profile, scoring low on both learning strategies. Conclusions: This study showed that we can use eye‐tracking to distinguish very strategic students, characterized using cognitive processing and regulation strategies, from low strategic students, characterized by a lack of cognitive and regulation strategies. These students processed the expository text according to how they self‐reported.